Perception on the performance of undergraduate library and information science majors as student assistants at selected University of the Philippines Diliman Libraries - Morandarte, Mary Jane C. (2009)
This study determines the perception of the staff from selected UP Diliman libraries on the performance of Library and Information Science majors working as student assistants. Thirty of the staff from the UP Main Library, College of Law Library, College of Engineering Library I and College of Engineering Library II answered the survey questionnaire that were distributed in the said libraries.